Advancements in the Development of Non‐Nitrogen‐Based Amphiphilic Antiseptics to Overcome Pathogenic Bacterial Resistance. (13th October 2020) - Carden, Robert G.; Sommers, Kyle J.; Schrank, Cassandra L.; Leitgeb, Austin J.; Feliciano, Javier A.; Wuest, William M.; Minbiole, Kevin P. C.
Abstract: The prevalence of quaternary ammonium compounds (QACs) as common disinfecting agents for the past century has led bacteria to develop resistance to such compounds. Given the alarming increase in resistant strains, new strategies are required to combat this rise in resistance. Recent efforts to probe and combat bacterial resistance have focused on studies of multiQACs. Relatively unexplored, however, have been changes to the primary atom bearing positive charge in these antiseptics. Here we review the current state of the field of both phosphonium and sulfonium amphiphilic antiseptics, both of which hold promise as novel means to address bacterial resistance. Abstract : Given the prevalence of QACs as disinfectants, bacteria have begun to develop resistance to these compounds at an alarming rate. Recent efforts to better understand and combat this resistance have featured multiQACs, with some other potential avenues still underexplored. Here we review the current state of both phosphonium‐ and sulfonium‐based amphiphilic disinfectants, which hold promise as classes of compounds to address increasing bacterial resistance.